Suppression of Rheumatoid Arthritis by Enhanced Lymph Node Trafficking of Engineered Interleukin‐10 in Murine Models. Issue 5 (8th March 2021) - Yuba, Eiji; Budina, Erica; Katsumata, Kiyomitsu; Ishihara, Ako; Mansurov, Aslan; Alpar, Aaron T.; Watkins, Elyse A.; Hosseinchi, Peyman; Reda, Joseph W.; Lauterbach, Abigail L.; Nguyen, Mindy; Solanki, Ani; et al.
Abstract : Objective: Rheumatoid arthritis (RA) is a major autoimmune disease that causes synovitis and joint damage. Although clinical trials have been performed using interleukin‐10 (IL‐10), an antiinflammatory cytokine, as a potential treatment of RA, the therapeutic effects of IL‐10 have been limited, potentially due to insufficient residence in lymphoid organs, where antigen recognition primarily occurs. This study was undertaken to engineer an IL‐10–serum albumin (SA) fusion protein and evaluate its effects in 2 murine models of RA. Methods: SA‐fused IL‐10 (SA–IL‐10) was recombinantly expressed. Mice with collagen antibody–induced arthritis (n = 4–7 per group) or collagen‐induced arthritis (n = 9–15 per group) were injected intravenously with wild‐type IL‐10 or SA–IL‐10, and the retention of SA–IL‐10 in the lymph nodes (LNs), immune cell composition in the paws, and therapeutic effect of SA–IL‐10 on mice with arthritis were assessed. Results: SA fusion to IL‐10 led to enhanced accumulation in the mouse LNs compared with unmodified IL‐10. Intravenous SA–IL‐10 treatment restored immune cell composition in the paws to a normal status, elevated the frequency of suppressive alternatively activated macrophages, reduced IL‐17A levels in the paw‐draining LN, and protected joint morphology. Intravenous SA–IL‐10 treatment showed similar efficacy as treatment with an anti–tumor necrosis factor antibody. SA–IL‐10 was equally effective when administered intravenously, locally, or subcutaneously, which is a benefit for clinical translation of this molecule. Conclusion: SA fusion to IL‐10 is a simple but effective engineering strategy for RA therapy and has potential for clinical translation.